1979
DOI: 10.2134/jeq1979.00472425000800010015x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Simulated Rainfall on the Retention of Sludge Heavy Metals by the Leaves of Forage Crops

Abstract: The land disposal of municipal liquid digested sludge by surface application to a growing forage crop may cause foliage to become coated with sludge. The ingestion of foliage contaminated with sludge could be detrimental to the health of grazing animals, since municipal sludges often contain potentially toxic amounts of various heavy metals. The influence of simulated rainfall, leaf morphology, and sludge solids concentration on the retention of sludge heavy metals by the foliage of grasses was evaluated.Liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…They suggested that other forage crops and sludges might have different results. This was confirmed by Jones et al (1979), who reported that Bell Rhodes grass (Chloris gayana) retained 58-67% more sludge than common Bermuda grass (Cynodon dactylon) because of its larger leaf blades, ligules and overlapping sheaths. The leaf area to mass ratios for both grasses were approximately equal.…”
Section: Adhesion Of Sludge Solidsmentioning
confidence: 62%
“…They suggested that other forage crops and sludges might have different results. This was confirmed by Jones et al (1979), who reported that Bell Rhodes grass (Chloris gayana) retained 58-67% more sludge than common Bermuda grass (Cynodon dactylon) because of its larger leaf blades, ligules and overlapping sheaths. The leaf area to mass ratios for both grasses were approximately equal.…”
Section: Adhesion Of Sludge Solidsmentioning
confidence: 62%
“…The results from this study indicate that the extent of gypsum adherence varies from those observed with biosolids. With biosolids, it has been shown that substantial adherence to forage and other plant species can be expected, especially if allowed to dry (Chaney et al, 1987; Jones et al, 1979). Also, rainfall events will not remove the adhering biosolids particles, which have been shown to persist throughout the growing season (Chaney and Lloyd, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, differences in biosolids adherence and persistence were noted between different forage species (Aitken, 1997; Chaney et al, 1987). Rainfall immediately after fluid biosolids application removed most of the initially adhering biosolids (Jones et al, 1979). Current USEPA guidelines state that biosolids should be applied to closely clipped forage and stipulates a 30‐d waiting period after surface application of biosolids before grazing is resumed.…”
mentioning
confidence: 99%
“…In several studies (Jones et al, 1979;Chaney and Lloyd, 1979;Klessa and Desira-Buttigieg, 1992;Aitken, 1997) conflicting evidence of binding of elements to herbage has been reported. Klessa and Desira-Buttigieg (1992) and Aitken (1997) used an 'adhesion index' (AI) to compare retention of metals on the day of sludge application: AI ¼ ðTreatment À controlÞ metal offtake Weight of metal applied Klessa and Desira-Buttigieg (1992) and Aitken (1997) used a similar experimental design, although the sludges used differed in DM content (2 and 68 g kg )1 , respectively).…”
Section: Adhesion Of Ptm To Herbage From Surface Applied Sewage Sludgementioning
confidence: 99%